Designing learning experiences on climate change for undergraduate students of different majors - Carrillo-Nieves, Danay; Clarke-Crespo, Emilio; Cervantes-Avilés, Pabel; Cuevas-Cancino, María; Vanoye-García, Ana Y. (Frontiers in Education, 2024)
Education about a complex topic as climate change faces an evolution of the knowledge, learning processes, students and even universities constrain. As we can adapt to these changes, we will be able to improve learning experiences for students. In this work, learning experiences about climate change were evaluated ion undergraduate students without engineering background, as function of the size of the group, duration of the course, gamification activities and technology and virtual tools experiences. The implementation of these activities ion the intensive 5-week course focused on climate change education,education has revealed valuable insights into student motivation, attitude, knowledge acquisition, and engagement. Notably, students' trust in information sources about climate change exhibited variations, with global organizations garnering higher confidence compared to local and personal sources. In Ecological Processes for Human Development course (DS1009), the diagnostic test highlighted a 53% understanding level, particularly challenging in numeric aspects. However, the Escape room significantly improved results in the final exam, demonstrating a 93% correctness rate, emphasizing the effectiveness of the activities in reinforcing key climate change concepts. The findings underscore the need for comprehensive climate change education, integrating not only scientific concepts but also ethical considerations, critical thinking, and interdisciplinary perspectives. On the other In other hand, the emergence of climate change-themed escape rooms as an engagement tool demonstrates their potential in enhancing knowledge acquisition and cooperative learning. Escape rooms offer an immersive environment that encourages active participation, enabling students to grasp complex climate concepts and solutions more effectively. The success of these tools relies on clear alignment with the course objectives and the use of innovative methods that resonate with today's technologically savvy generation. The study underscores that climate education should go beyond facts, emphasizing universities' crucial role in nurturing the "climate change generation" with the knowledge and motivation for meaningful contributions to climate action and policy formulation.